2009
DOI: 10.1080/14733140903032208
|View full text |Cite
|
Sign up to set email alerts
|

‘Extra appendage’ or integrated service? School counsellors' reflections on their professional identity in an era of education reform

Abstract: Aims: Since 2003, Government policies have located increasing responsibility for children's well‐being on schools working in partnership with other agencies. This study sought to investigate how these policies affect the working lives and professional identities of counsellors in schools in challenging circumstances in England. Method: In‐depth interviews with six school counsellors (4 primary and 2 secondary). Transcripts were analysed using Interpretive Phenomenological Analysis to reveal five master themes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…External practitioners can be faced with a difficult decision about whether to optimise their service within existing school structures or to try and re-shape those structures, especially where they conflict with or undermine their work. Our research suggests it may be unrealistic for services such as Bounceback to take on this process, a finding which echoes those of Harris (2009) who also noted the significant emotional demands such conflicts can generate in practitioners such as school-based counsellors. Schools are tasked with and primarily judged by their educational success, with multiple time pressures and the need to timetable activities.…”
Section: Discussionsupporting
confidence: 49%
“…External practitioners can be faced with a difficult decision about whether to optimise their service within existing school structures or to try and re-shape those structures, especially where they conflict with or undermine their work. Our research suggests it may be unrealistic for services such as Bounceback to take on this process, a finding which echoes those of Harris (2009) who also noted the significant emotional demands such conflicts can generate in practitioners such as school-based counsellors. Schools are tasked with and primarily judged by their educational success, with multiple time pressures and the need to timetable activities.…”
Section: Discussionsupporting
confidence: 49%
“…The extensive discussions about the need for, and the concerns on how to work with families further support the prospects for more dialogue and collaboration between stakeholders to develop a comfortable tripartite working relationship. As suggested in earlier studies, the quality of working relationships among stakeholders is an important aspect of an effective school counselling service (Cromarty & Richards, 2009;Harris, 2009). Chong et al (2013) and Kok (2013) also recommended closer collaborative working relationships between stakeholders.…”
Section: Discussionmentioning
confidence: 97%
“…Harris' (2009) in-depth study of the experiences of six school counsellors found that those without dual roles in school felt like 'outsiders' on the margins of school life. Without a supportive relationship with the school leaders, counsellors felt vulnerable to pressures within schools, particularly to take into counselling disruptive children who risked being excluded.…”
Section: Literature Reviewmentioning
confidence: 98%